ЗАХІДНОПОЛІСЬКІ ПРІЗВИСЬКА, СПІВВІДНОСНІ З ПРІЗВИСЬКАМИ ЖИТЕЛІВ ЛЬВІВЩИНИ - Наливайко, Марія (My University, 2010)
У статті проаналізовано західнополіські відапелятивні прізвиська, співвідносні з прізвиськами жителів Львівщини. Для порівняльної характеристики прізвиськ виділено дванадцять лексико-тематичних груп. In the article the nicknames of Lvivshchina, formed from the common names wich correlative with the nicknames of inhabitants of the Lviv region are analysed. The lexical-thematic groups are selected for system description.
Keywords: прізвисько; лексико-тематична група; nickname; lexical-thematical group